Improving of UHF RFID pattern steering by phased antenna array - Branislav, Krnac; Jan, Haring (2008)
Radio Frequency Identification (RFID) is very potential technology suitable for various areas of applications. From utilization in the supply chain. thought traffic application to livestock tracking and persons identification and verification. Current passive RFID UHF tags are non-directional and have general radiation pattern characteristic. By managing the direction of the pattern we can gain more time required for accomplishment sophisticated functions of IC and the energetic feed increases as well. These facilities make RFID technology suitable for more advanced applications as position determination and localization in wireless ad-hoc networks. This article deals with passive open-ended two strips UHF tag reading range and possibilities of enhancing this range by utilization of intelligent antenna set in RFID tag.